Comparative study of hybrid and nanofluid flows over an exponentially stretched curved surface with modified Fourier law and dust particles. Issue 6 (2nd November 2022) - Alotaibi, Hammad; Ramzan, Muhammad
Abstract : Hybrid nanofluids are the prospective liquids that possess improved heat transfer enactment and thermophysical characteristics than conventional heat transfer fluids (water, oil, ethylene glycol) and single-particle nanoparticle immersed nanofluids. Here, a comparison of the hybrid nanofluid comprising copper, copper oxide nanosized particles with ethylene glycol (Cu-CuO/C2 H6 O2 ) as the customary liquid, with nanofluid copper-ethylene glycol (Cu/C2 H6 O2 ) is made. The flow of hybrid nanofluid is considered over an absorbent curved sheet which is stretched exponentially with dust particles with modified Fourier law. The modeled problem is assisted by the melting heat and second-order slip boundary conditions. The system of equations is coped numerically after applying the boundary layer theory to the system of governing equations. It is witnessed that dust phase and temperature are augmented for escalating estimations of the curvature parameter. It is also perceived that an escalation in the thermal relaxation and concentration parameter values results in a lowering temperature of the fluid. Furthermore, it is remarked that fluid velocity is enhanced for large disk curvature. The hybrid nanofluid in case of heat transfer comparison is far ahead of the nanofluid. The acquired outcomes are also endorsed by making a comparison with a published study. An outstanding agreement is attained.